FROM COUNTER DAEMONS: ORACLE AND 4D. - Harrison, Roberto (Mandorla, 2005)
The author introduces his poem "From Counter Daemons." He claims that there are few computer science ideas that form the basis of the poem. He defines the computer jargon daemon. He explains that counter variables are used by computer programmers to count the times a program has gone through a processing loop.